The image of a Horse in Yakut and Khakass Heroic Epic: Based on Yakut Olonkho and Khakass Alyptyh Nymah - Bozhedonova, Alla Evgenievna; Ivanov, Vasily Nikolaevich (Journal of History Culture and Art Research, 2019)
The article is devoted to a comparative analysis of the image of the epic horse in the texts of two related Turkic epics. The material for the research in a comparative aspect was the texts of the Yakut epic “The Girl-Warrior of Dzhyrybyna Dzhyrylyatta with a milk-white horse” by P. P. Yadrikhinsky – Bedjeele and “Son of the Horse Dyyray Warrior” by I. I. Burnasheva – Tong Suorun; Khakass epic “Altyn-Aryg” by S. P. Kadyshev and “Ai-Khuuchin” by P. V. Kurbizhekov. The choice of these texts is due to the fact that their academic publications are equipped with a good reference apparatus, as well as the presence of facing Russian translation and relatively equal volume of texts. The relevance of the study is determined by the increasing interest in the comparative study of Turkic epics. The subject of this study is the image of an epic horse from the texts of the Yakut olonkho and Khakass alyptyh nymah. The purpose of this article is to identify the commonality and differences in the images of the epic horse in the epics of related Turkic peoples. In order to achieve this objective, сontrastive-сomparative and comparative-historical methods were used to identify the general and specific in the Turkic epics and a descriptive method that allows us to more deeply characterize the image of the epic horse taking into account the worldview and mentality of these peoples. The analysis showed that the horse is present in all the main events of the life of the epic bogatyr accompanying him in all significant events. A commonplace in the image of a horse for the Yakut and Khakass heroic epics is a beautiful description of a horse, loyalty and power of a horse, as well as its ability to speak in human language. A wide variety of horse’s colors in epics indicates good knowledge of Turkic peoples in horse breeding. The image of the horse, which had a major impact, refers to the archetypal symbols of the culture of the Turkic people.